Relocations in the city of Encarnación, Paraguay: urban and socio-economic effects - Gimenez Castro, Gloria (2019)
This paper is about the problem of the socioeconomic conditions of the homes relocated by the Yacyretá Hidroelectric Proyect in the city of Encarnación, Paraguay. Such approach analyzes the uncertainty and vulnerability generated by the relocation and socio-urban transformation programs.In this sense, the objective is to know and characterize the economic, labor and health problems that families are going through and, at the same time, analyze what are the main daily adversities that the population must face. Methodologically, the research starts from a mixed approach, quantitative and qualitative approach with descriptive design, since the research focuses on knowing aspects related to subsistence practices, within the framework of the socioeconomic and environmental vulnerability of families, analyzing dimensions related to culture, to understand how is the way of life resettled families, the experience of the changes in the order of socio-housing and economic processes.